The Factors Improving the Quality of Local Government Financial Reporting Performance: A Mini Review Approach - Harahap, Angginun Juwita Sari; Erlina, Erlina (West Science Business and Management, 2024)
The goal of this research is to investigate the variables applying accounting standards, internal control, using information technology, and the caliber of human resources that impact the caliber of local government financial reporting. Using the literature review method, this research examines various journals, articles, and books related to the topic under study. The findings indicate that the execution of Government Accounting Standards (SAP) significantly improves the transparency and accountability of financial statements. A strong internal control system helps reduce errors and fraud, while the utilization of information technology, such as accounting information systems, contributes to increasing the effectiveness and precision of financial reporting. For the purpose of maximizing the application of internal controls and accounting standards, the caliber of qualified human resources became crucial. This study advocates for local governments to enhance SAP adoption, fortify internal controls, optimize information technology usage, and cultivate human resource capabilities to attain superior financial reporting quality.